International Continental Scientific Drilling Program (ICDP) workshop on the Fucino paleolake project: the longest continuous terrestrial archive in the MEditerranean recording the last 5 Million years of Earth system history (MEME) - B. Giaccio; B. Wagner; G. Zanchetta; A. Bertini; G. P. Cavinato; R. de Franco; F. Florindo; D. A. Hodell; T. A. Neubauer; S. Nomade; S. Nomade; A. Pereira; et al. (Scientific Drilling)
During the last 5 million years (Pliocene–Holocene), the Earth climate system has undergone a series of marked changes, including (i) the shift from the Pliocene warm state to the Pleistocene cold state with the intensification of Northern Hemisphere glaciation; (ii) the evolution of the frequency, magnitude, and shape of glacial–interglacial cycles at the Early Middle Pleistocene Transition (∼ 1.25–0.65 Ma); and (iii) the appearance of millennial-scale climate variability. While much of this paleoclimate narrative has been reconstructed from marine records, relatively little is known about the impact of these major changes on terrestrial environments and biodiversity, resulting in a significant gap in the knowledge of a fundamental component of the Earth system. Long, continuous, highly resolved, and chronologically well-constrained terrestrial records are needed to fill this gap, but they are extremely rare. To evaluate the potential of the Fucino Basin, central Italy, for a deep-drilling project in the framework of the International Continental Scientific Drilling Program (ICDP), 42 scientists from 14 countries and 32 institutions met in Gioia dei Marsi, central Italy, on 24–27 October 2023 for the ICDP-supported MEME (the longest continuous terrestrial archive in the MEditerranean recording the last 5 Million years of Earth system history) workshop. The existing information and unpublished data presented and reviewed during the workshop confirmed that the Fucino Basin fulfils all the main requisites for improving our understanding of the mode and tempo of the Plio-Quaternary climatic–environmental evolution in a terrestrial setting at different spatial and temporal scales. Specifically, the combination of the seismic line evidence with geochronological and multi-proxy data for multiple sediment cores consolidated the notion that the Fucino Basin infill (i) is constituted by a sedimentary lacustrine succession continuously spanning at least 3.5 Myr; (ii) has a high sensitivity as a paleo-environmental–paleoclimatic proxy; and (iii) contains a rich tephra record that allows us to obtain an independent, high-resolution timescale based on tephrochronology. Considering the typical half-graben, wedge-shaped geometry of the basin, four different potential drilling targets were identified: MEME-1, located in the middle of the basin, should reach the base of the Quaternary infill at ∼ 500 m depth; MEME-2, located west of MEME-1, has sedimentation rates that are lower, with the base of the Pliocene–Quaternary at ∼ 600 m depth; MEME-3b has the same target as MEME-2 but is located further west, where the base of the Pliocene–Quaternary should be reached at ∼ 300 m; and MEME-3a (∼ 200–300 m depth) is located, for tectonic purposes, on the footwall of the basin master fault. Overall, the MEME workshop sets the basis for widening the research team and defining the scientific perspectives and methodological approaches of the project, from geophysical exploration to the development of an independent chronology and to the acquisition of multi-proxy records, which will contribute to the preparation of the full MEME proposal.